Do the right thing - Lee, Spike 1957-; Lee, Spike 1957-; Dickerson, Ernest R. 1951-; Davis, Ossie 1917-2005; Dee, Ruby 1922-2014; Aiello, Danny 1933-2019; Edson, Richard 1954-; Esposito, Giancarlo 1958-; Nunn, Bill 1953-2016; Turturro, John 1957-; Faison, Frankie R. 1949-; Jackson, Samuel L. 1948-; et al. (Universal Pictures International limited, 2001)
Traces the course of a single day on a block in the Bedford-Stuyvesant area of Brooklyn, New York.
Original: USA, 1989
Enthält Zusatzmaterial
Keywords: Feature films; Films for the hearing impaired; Race relations in motion pictures; Italiener; Schwarze; USA; Film; DVD-Video